1982
DOI: 10.1055/s-2007-1019026
|View full text |Cite
|
Sign up to set email alerts
|

Alpha2-Macroglobulin and Proliferative Retinopathy in Type 1 Diabetes

Abstract: Serum alpha 2-macroglobulin (alpha 2m) and total glycosylated haemoglobin (HbA1) concentrations were measured in 110 insulin dependent Type 1 diabetics with minimal or no fundoscopic retinopathy, referred to as non-retinopaths, and in 52 proliferative retinopaths. Proteinuria was recorded in 8 (7%) non-retinopaths and 29 (56%) retinopaths and was accompanied by elevated alpha 2m concentrations in both groups of diabetics but only significantly so in the non-retinopaths. Diabetics without proteinuria showed a s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 9 publications
0
10
0
1
Order By: Relevance
“…In patients with NAFLD we previously demonstrated a very significant association between A2M and insulin levels, a hallmark of insulin resistance [25]. Other studies have observed an increase of A2M in diabetic patients [41]. Insulin is covalently bound to A2M [42] in plasma and A2M is a binding protein of Insulin-like Growth Factor Binding Protein-1 (IGFBP-1) which modifies the IGFBP-1/IGF interaction [43].…”
Section: Discussionmentioning
confidence: 99%
“…In patients with NAFLD we previously demonstrated a very significant association between A2M and insulin levels, a hallmark of insulin resistance [25]. Other studies have observed an increase of A2M in diabetic patients [41]. Insulin is covalently bound to A2M [42] in plasma and A2M is a binding protein of Insulin-like Growth Factor Binding Protein-1 (IGFBP-1) which modifies the IGFBP-1/IGF interaction [43].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed that induced hyperglycemia in normal nondiabetic persons results in increased serum concentrations of a 2 M (14). Furthermore, evidence is mounting that elevated a 2 M levels are seen in diabetics with increased risk of microangiopathic complication, retinopathy, and nephropathy (58)(59)(60)(61). An interesting observation has been made suggesting that patients with prostate cancer and bone metastases had extremely low levels of a 2 M (62-64).…”
Section: Discussionmentioning
confidence: 99%
“…Of note, we found increased expression of several proteins, including a2-macroglobulin, vitamin D-binding protein, and prostaglandin-H2 Disomerase, which have been proposed as biomarkers for diabetes mellitus. [22][23][24][25][26][27] In recent years, there has been accumulating evidence showing that IVI increases the risk of TRD in patients with severe PVR. 9,[14][15][16][17][18] However, the molecular mechanism underlying the profibrotic effects of anti-VEGF drugs is not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…We also found differential expression in a2-macroglobulin, vitamin D-binding protein, and prostaglandin-H2 D-isomerase, which were previously referred to as biomarkers for diabetes mellitus. [22][23][24][25][26][27] In addition, the proteins ceruloplasmin, a-synuclein, flavin reductase, glutathione peroxidase-3, catalase, and peroxiredoxin-2 were differentially expressed among the three groups. The signal intensities for the differentially expressed proteins are shown in Supplementary Table S3.…”
Section: Vh Proteome In Eyes With Pdrmentioning
confidence: 99%